The visibility mindset how Asian American leaders create opportunities and push past barriers - Chao, Bernice M.; Lam, Jessalin (Ascent Audio, 2022)
Explore the challenges faced by Asian professionals and how to overcome them Find your voice, own your story, and elevate your professional life. In The Visibility Mindset: How Asian American Leaders Create Opportunities and Push Past Barriers, a team of dedicated creative professionals and educators delivers an incisive treatment addressing the importance of cultural upbringing in our lives and careers. In the book, you'll explore the varied realities and experiences of Asian Americans in the diasporic Asian community and how they have impacted the personal and professional lives of real people. The authors also discuss: the model minority myth, bamboo ceilings, and other stereotypes that have barred Asians from leadership ranks for decades; straightforward exercises, strategies, and real-life examples of how to break down career barriers to advancement; and stories from leaders across a variety of industries addressing how they personally overcame many of the challenges discussed in the book. A can't-miss guide for Asian professionals and allies, The Visibility Mindset is also an ideal resource for executives, managers, and other business leaders seeking to make their organization fairer, more diverse, and more equitable.
Online resource; title from title details screen (O'Reilly, viewed January 5, 2023)
Keywords: Leadership -- United States; Career development -- United States; Asian Americans -- Social conditions; Leadership; États-Unis; Plan de carrière; États-Unis; Américains d'origine asiatique; Conditions sociales; Asian Americans; Social conditions; Career development; Leadership; United States; Audiobooks; Livres audio